Identification of the changes in the platelet proteomic profile of elderly individuals - Chen, Hui-Lian; Wang, Qing-Yu; Qi, Ruo-Mei; Cai, Jian-Ping (Frontiers in Cardiovascular Medicine, 2024)
Background Platelet hyperreactivity is a risk factor for thrombosis in elderly patients with cardiovascular diseases. However, the mechanism of platelet hyperactivation has not been elucidated. This study aims to investigate alterations in the proteomes of platelets and their correlation with platelet hyperreactivity among elderly individuals. Methods This study included 10 young (28.1 ± 1.9 years), 10 middle-aged (60.4 ± 2.2 years), and 10 old (74.2 ± 3.0 years) subjects. Washed platelets were used in the present study. Platelet samples were analysed by using data-independent acquisition (DIA) quantitative mass spectrometry (MS). Results The results showed that the platelet proteomic profile exhibited high similarity between the young and middle-aged groups. However, there were significant differences in protein expression profiles between the old group and the young group. By exploring the dynamic changes in the platelet proteome with ageing, clusters of proteins that changed significantly with ageing were selected for further investigation. These clusters were related to the initial triggering of complement, phagosome and haemostasis based on enrichment analysis. We found that platelet degranulation was the major characteristic of the differentially expressed proteins between the old and young populations. Moreover, complement activation, the calcium signalling pathway and the nuclear factor-κB (NF-κB) signalling pathway were enriched in differentially expressed proteins. Conclusions The present study showed that there are obvious differences in the protein profiles of the elderly compared with young and middle-aged populations. The results provide novel evidence showing changes in platelet hyperactivity and susceptibility to thrombosis in the elderly population.